DIMENSI AKSIOLOGIS FILSAFAT HIDUP PIIL PESENGGIRI DAN RELEVANSINYA TERHADAP PENGEMBANGAN KEBUDAYAAN DAERAH LAMPUNG - Himyari Yusuf (Fakultas Filsafat, Universitas Gadjah Mada Yogyakarta, 2010)
AbstractThe way of life of Lampung people, Piil Pesenggiri, essentially is related to existence of human being correlating to God, other human, and nature. From the axiological dimension, Piil Pesengiri contains some values, such as divinity, religiousity, spirituality, morality, intellectuality, individuality, sociality, andmaterial. Those values can be pressed into three values: divinity, humanity, and vitality.Strategy of cultural development in Lampung must refer to the values of Piil Pesenggiri. It focus on political system of leadership/ power, economy, environment and education. Thereason is governmental, economical, and environmental policyphilosophically can impact and form mindset and lifestyle of Lampung people.Keywords: Piil Pesenggiri, value of divinity, value of humanity,value of vitality.